2014
DOI: 10.5751/es-06264-190224
|View full text |Cite
|
Sign up to set email alerts
|

Ecohealth and Resilience Thinking: A Dialog from Experiences in Research and Practice

Abstract: ABSTRACT. Resilience thinking and ecosystems approaches to health (EAH), or ecohealth, share roots in complexity science, although they have distinct foundations in ecology and population health, respectively. The current articulations of these two approaches are strongly converging, but each approach has its strengths. Resilience thinking has developed theoretical models to the study of socialecological systems, whereas ecohealth has a vast repertoire of experience in dealing with complex health issues. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 86 publications
0
19
0
3
Order By: Relevance
“…Using discrete time models fitted to population time-series data, Holdo et al (2009) have showed how suppression of endemic rinderpest in the wildebeest population caused the Serengeti ecosystem to increase its woody component by a factor of two to three, consequently facilitating its switch from a net carbon source to a net carbon sink over a 40-year period. Further examples of social processes producing ecological feedbacks with social consequences come from the ecohealth and landscape epidemiology literatures, with many studies now drawing the link between landscape degradation, pathogen spread, and negative consequences for human health and well-being (see Myers et al 2013, Berbés-Blázquez et al 2014 for examples).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using discrete time models fitted to population time-series data, Holdo et al (2009) have showed how suppression of endemic rinderpest in the wildebeest population caused the Serengeti ecosystem to increase its woody component by a factor of two to three, consequently facilitating its switch from a net carbon source to a net carbon sink over a 40-year period. Further examples of social processes producing ecological feedbacks with social consequences come from the ecohealth and landscape epidemiology literatures, with many studies now drawing the link between landscape degradation, pathogen spread, and negative consequences for human health and well-being (see Myers et al 2013, Berbés-Blázquez et al 2014 for examples).…”
Section: Discussionmentioning
confidence: 99%
“…Protected area resilience, in the sense of specified, normatively positive resilience, can be thought of as the ability of the social-ecological system to maintain key elements of its identity in space and time, through various perturbations and changes (Cumming et al 2005). It is important to note that resilience, as used here, does not imply that systems should bounce Although there are comparatively few articles on resilience and disease published in mainline conservation, ecosystem services, and resilience journals, the relatively young fields of landscape epidemiology (Meentemeyer et al 2012, Myers et al 2013) and ecohealth (e.g., Berbés-Blázquez et al 2014) have produced a swath of recent literature contextualizing the social-ecological and complex nature of disease. The one health paradigm (D'Amico Hales et al 2004, Cumming and Atkinson 2012, Cumming and Cumming 2015 in particular promises to be influential in the development of new conservation policies and strategies that recognize that human and ecological health are inherently linked.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different schools of thought in complex systems and resilience theories illustrate important features of how social-ecological systems work (Turner 2014). One commonality among these schools of thought, however, is that they can be (and frequently are) applied in depoliticized ways that ignore power dynamics (Berbés-Blázquez et al 2014;Hornborg 2013;McGreavy 2016). Walker and Cooper (2011), for example, point out how resilience thinking resonates with dominant manifestations of neoliberal ideology (7), such as the view that 'there is no alternative' to market-dominated economic globalization.…”
Section: Ecohealth Neoliberalism and Complex Systems Theoriesmentioning
confidence: 99%